2022
DOI: 10.31015/jaefs.2022.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of antimicrobial properties and chemical composition of different extracts of Sweet gum leaves (Liquidambar orientalis)

Abstract: Different extracts of Liquidambar orientalisleaves were tested for their antimicrobial activity against eleven bacterial and one yeast strain by disc diffusion method. The antimicrobial activity was measured by disc diffusion and MIC. After that among extracts the best antimicrobial activity was detected.Volatile components of the ethanolic extracts of leaves of sweetgum analysed by GC/MS. Ethanolic extracts of sweetgum leaves showed the best inhibition zones against Klebsiella pneumoniae (32mm). K.pneumoniae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The bioactive phytochemicals benzenemethanol, alpha-(1-aminoethyl)-in Ribwort plantain (Haghighi et al, 2022), 3-tert-butyl-5-chloro-2-hydroxybenzophenone in the Tamarindus indica (Fagbemi et al, 2021), cyclotetrasiloxane, octamethyl-in Olea europaea (Keskin et al, 2012), N-(Trifluoroacetyl)-N,O,O',O'-tetrakis (trimethylsilyl) norepinephrine in the red sea cucumber Holothuria atra (Soliman et al, 2016), cyclohexasiloxane, dodecamethyl-in Argemone ochroleuca (Moustafa et al, 2013), cycloheptasiloxane, tetradecamethyl-in Senna auriculata (Prasathkumara et al, 2021), cyclooctasiloxane, hexadecamethyl-in Sedum pallidum (Dahpour et al, 2012), heptasiloxane, 1,1,3,3,5,5,7,7,9,9,11,11,13,13tetradecamethyl-in Olea europaea (Mukesi et al, 2019 in Moringa oleifera (Falowo et al, 2017) identified in previous studies to have antibacterial properties are identified in the methanolic extracts of W. somnifera vegetative stem. The phytochemicals in methanolic extracts of stem from W. somnifera, Cyclononasiloxane, octadecamethyl-, were found to be antibacterial as well as antifungal in Salvadora persica (Bratty et al, 2020), 3-amino-1,2-propanediol as antifungal in Solanum khasianum (Chirumamilla et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The bioactive phytochemicals benzenemethanol, alpha-(1-aminoethyl)-in Ribwort plantain (Haghighi et al, 2022), 3-tert-butyl-5-chloro-2-hydroxybenzophenone in the Tamarindus indica (Fagbemi et al, 2021), cyclotetrasiloxane, octamethyl-in Olea europaea (Keskin et al, 2012), N-(Trifluoroacetyl)-N,O,O',O'-tetrakis (trimethylsilyl) norepinephrine in the red sea cucumber Holothuria atra (Soliman et al, 2016), cyclohexasiloxane, dodecamethyl-in Argemone ochroleuca (Moustafa et al, 2013), cycloheptasiloxane, tetradecamethyl-in Senna auriculata (Prasathkumara et al, 2021), cyclooctasiloxane, hexadecamethyl-in Sedum pallidum (Dahpour et al, 2012), heptasiloxane, 1,1,3,3,5,5,7,7,9,9,11,11,13,13tetradecamethyl-in Olea europaea (Mukesi et al, 2019 in Moringa oleifera (Falowo et al, 2017) identified in previous studies to have antibacterial properties are identified in the methanolic extracts of W. somnifera vegetative stem. The phytochemicals in methanolic extracts of stem from W. somnifera, Cyclononasiloxane, octadecamethyl-, were found to be antibacterial as well as antifungal in Salvadora persica (Bratty et al, 2020), 3-amino-1,2-propanediol as antifungal in Solanum khasianum (Chirumamilla et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In a study, AgNPs produced from the Sida cordifolia plant were reported to be effective on B. subtilis bacteria at the concentration of 6.25 mg/mL (Pallela et al, 2018). In another study, the MIC value of biological AgNPs produced from Streptomyces xinghaiensis OF1 strain for S. aureus was reported as 256 mg/mL (KESKİN & GÜVENSEN, 2022;Wypij et al, 2018).…”
Section: Crystal Structure Analysis (Xrd) Of Agnpsmentioning
confidence: 99%
“…Therefore it is necessary to investigate alternative medicines or natural treatment methods to overcome such side-effects of current drugs. There are many studies in the literature describing the antidiabetic activity of plant extracts (Temiz, 2021;Keskin et al, 2022). There are investigations depicting that pomegranate (Alsataf et al, 2021) and Quercus infectoria (Başyiğit et al, 2020) display antidiabetic activity.…”
Section: Antidiabetic Activities Of Free Esterified and Bound Phytoch...mentioning
confidence: 99%